Development of a one-run real-time PCR detection system for pathogens associated with bovine respiratory disease complex - KISHIMOTO, Mai; TSUCHIAKA, Shinobu; RAHPAYA, Sayed Samim; HASEBE, Ayako; OTSU, Keiko; SUGIMURA, Satoshi; KOBAYASHI, Suguru; KOMATSU, Natsumi; NAGAI, Makoto; OMATSU, Tsutomu; NAOI, Yuki; SANO, Kaori; et al. (Journal of Veterinary Medical Science, 2017)
Bovine respiratory disease complex (BRDC) is frequently found in cattle worldwide. The etiology of BRDC is complicated by infections with multiple pathogens, making identification of the causal pathogen difficult. Here, we developed a detection system by applying TaqMan real-time PCR (Dembo respiratory-PCR) to screen a broad range of microbes associated with BRDC in a single run. We selected 16 bovine respiratory pathogens (bovine viral diarrhea virus, bovine coronavirus, bovine parainfluenza virus 3, bovine respiratory syncytial virus, influenza D virus, bovine rhinitis A virus, bovine rhinitis B virus, bovine herpesvirus 1, bovine adenovirus 3, bovine adenovirus 7, Mannheimia haemolytica, Pasteurella multocida, Histophilus somni, Trueperella pyogenes, Mycoplasma bovis and Ureaplasma diversum) as detection targets and designed novel specific primer-probe sets for nine of them. The assay performance was assessed using standard curves from synthesized DNA. In addition, the sensitivity of the assay was evaluated by spiking solutions extracted from nasal swabs that were negative by Dembo respiratory-PCR for nucleic acids of pathogens or synthesized DNA. All primer-probe sets showed high sensitivity. In this study, a total of 40 nasal swab samples from cattle on six farms were tested by Dembo respiratory-PCR. Dembo respiratory-PCR can be applied as a screening system with wide detection targets.